Same-sex Marriage - Hooper, Jennifer (Encyclopedia of the American Presidency, 2017)
The most up-to-date reference of its kind, Encyclopedia of the American Presidency, Third Edition is the definitive guide to the role of the president from the American Revolution through the present day.
Google-Books-ID: 4EmJwwEACAAJ
Keywords: dept.psc

Campaign Finance - Hooper, Jennifer (Encyclopedia of the American Presidency, 2017)
The most up-to-date reference of its kind, Encyclopedia of the American Presidency, Third Edition is the definitive guide to the role of the president from the American Revolution through the present day.
Google-Books-ID: 4EmJwwEACAAJ
Keywords: dept.psc

War on Terror - Hooper, Jennifer (Encyclopedia of the American Presidency, 2017)
The most up-to-date reference of its kind, Encyclopedia of the American Presidency, Third Edition is the definitive guide to the role of the president from the American Revolution through the present day.
Google-Books-ID: 4EmJwwEACAAJ
Keywords: dept.psc

Affordable Care Act - Hooper, Jennifer (Encyclopedia of the American Presidency, 2017)
The most up-to-date reference of its kind, Encyclopedia of the American Presidency, Third Edition is the definitive guide to the role of the president from the American Revolution through the present day.
Google-Books-ID: 4EmJwwEACAAJ
Keywords: dept.psc

Predicting revolt: Fragility indexes and the level of violence and instability in the Arab Spring - Buterbaugh, Kevin Neil; Calin, Costel; Marchant-Shapiro, Theresa (Terrorism and Political Violence, 2017)
This article is one of the first to systematically assess the ability of state fragility measures to predict violent protests and adverse regime changes in countries. We focus on the Arab Spring as an example of a situation that such measures ought to predict. Through a variety of analyses, we find that none of the measures are predictive. We then create a simple model using the literature of protest and revolts to predict both the level of violence and the extent of regime change in the Arab Spring countries. This simpler model does a better job of predicting the level of involvement in the Arab Spring than any of the complex State Fragility Indexes. Thus, the goal of this article is not to explain the causes of the Arab Spring, but to add to the discussion of the predictive value of measures of instability.
7 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000400285900008, lens.org/012-623-182-027-278 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: Arab Awakening; Arab Spring; Arab awakening; Arab spring; Political violence; Protest; State Fragility Indexes; State fragility; State fragility indexes; dept.psc; political violence; protest; state fragility

Presidential Framing in the 21st Century News Media: The Politics of the Affordable Care Act - Hopper, Jennifer Rose (Routledge, 2017)
The Patient Protection and Affordable Care Act came into existence at a time when the president’s ability to lead the public was in question, political polarization had intensified, and the media environment appeared ever more fragmented, fast-moving, and resistant to control. Under such circumstances, how can contemporary American presidents such as Barack Obama build and maintain support for themselves and their policies, particularly as controversies arise? Using case studies of major contests over how key elements of the Affordable Care Act would be framed, and analysis of how those frames fared in influential and popular U.S. news sources, Hopper examines the conditions under which the president can effectively shape public debates today. She argues that despite the difficult political and communications context, the president retains substantial advantages in framing major controversial issues for the media and the public. These presidential framing advantages are conditional, however, and Hopper explores the factors that help make presidential frames more or less likely to gain hold in the news today. More so than in the past, an element of unpredictability in this news environment means that in pursuing favorable messaging, the president and his surrogates may also generate some unintentional consequences in how issues are portrayed to the public. Presidential frames can evolve with unfolding events to take on new meanings and applications, a process facilitated alternately by supporters, opponents, and media actors. Still, media figures and political opponents remain largely reactive to presidential communications, even as some seek to publicize and exploit weaknesses in the administration’s narratives. A close look at these recent cases casts new light on the scholarly debate surrounding the president’s ability to persuasively communicate and challenges conventional wisdom that the 21st century media largely present an unmanageable news environment for the White House. Presidential Framing in the 21st Century News Media engages with current events in American politics, focusing on the Obama Administration and the Affordable Care Act, while also reflecting upon the state of the American presidency, the news media, and the public in ways that have substantial implications for all of these actors, not merely in the present, but into the future, making it a compelling read for scholars of Political Science, Media Studies, Communication Studies, and Public Policy. © 2017 Taylor & Francis.
Keywords: Public opinion; United States. Patient Protection and Affordable Care Act; Health care reform; United States; Medical policy; United States; Medicare; dept.psc; faculty_collection

Greece and the birth of containment: An American perspective - Iatrides, John O. (The Balkans in the Cold War, 2017)
America’s strategy of containment, designed to confront postwar Soviet aggression, real and perceived, grew out of a series of disparate and seemingly unrelated conflicts. Thus the clash over the future of defeated Germany was direct, immediate and of obvious importance for vital United States interests in Europe and the world. By contrast, the communist insurgency in Greece was originally perceived as a basically domestic affair of a small country in a remote region of little strategic value. Yet the Truman Doctrine, which paved the way for containment’s gradual global implementation—Marshall Plan, Berlin airlift, NATO, wars in Korea and Indochina—was ostensibly focused primarily on Greece. After remaining a benevolent but deliberately passive observer of turmoil and violence in Greece, Washington boldly replaced Britain as the foreign patron of that small and troubled Balkan state. This study documents the transformation of United States policy toward Greece, and the birth of containment. It argues that the change was fundamentally one of perceptions of the nature of Soviet policy itself within the Truman administration, rather than of realities in Greece. In retrospect, Greece was an unlikely springboard for launching the strategy of containing Moscow’s ideology and power. The significance of the communist threat in Greece was more a matter of alarmist assumptions, loose perceptions and questionable symbolism than of hard facts and geostrategic realities. But in human affairs perceptions and symbolism are important, especially if clothed in an aura of success, as was the application of containment in Greece.
Citation Key Alias: lens.org/005-990-706-119-140
Keywords: American Official; Greek Government; Military Assistance; North Atlantic Treaty Organization; Security Interest; dept.psc